Bariery inwestowania w energetykę wiatrową w Polsce - Pultowicz, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In the last few months, wind power sector has been developing very intensively (exponential growth). There are realistic chances for doubling this year's capacity installed in Poland in 2006, but there are many essential obstacles, which may make difficult to succeed. The goal of the article is to indicate, analyze and rank current barriers of wind power in Poland. Especially, the study outlines the need for minimalization or liquidation of barriers and shows new ways for improving wind power in Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 491-501